Brucea javanica Oil Emulsion Promotes Breast Cancer Cell Autophagy and Apoptosis by Regulating PAX6 mRNA Stability Through the hsa_circ_0001589/ G3BP1 Axis - Ke Li; MeiXia Li; XueQiang Pan; JiaWen Xu; Rui Jiang (Clinical and Experimental Pharmacology and Physiology, 2026)
ABSTRACT Background and Objective Brucea javanica oil emulsion (BJOE), a traditional Chinese medicine extract, has been demonstrated to possess antitumor activity in multiple cancers. However, its molecular mechanisms in breast cancer, particularly those involving circRNAs, remain unclear. This study investigates whether BJOE exerts its anti‐breast cancer effects by inducing autophagy and apoptosis through regulating hsa_circ_0001589/G3BP1/PAX6 signalling axis. Methods After BJOE treatment of MCF‐7 cells, cell viability, apoptosis (Annexin V‐FITC/PI staining) and autophagy (LC3‐II/LC3‐I ratio, autophagosome formation) were assessed. qPCR identified hsa_circ_0001589 as a key circRNA downregulated BJOE. RNA immunoprecipitation (RIP) and Western blot confirmed the interaction between hsa_circ_0001589 and G3BP1 and subsequent PAX6 inhibition. This axis was verified via functional rescue experiments (siRNA knockdown/overexpression). Results BJOE markedly inhibited MCF‐7 cells proliferation, induced apoptosis and activated autophagy in a dose‐dependent manner. Mechanistically, BJOE downregulated hsa_circ_0001589, thereby weakening the interaction between hsa_circ_0001589 and G3BP1 and reducing G3BP1‐mediated stabilisation of PAX6 mRNA. Silencing hsa_circ_0001589 mimicked the effects of BJOE, whereas overexpression of hsa_circ_0001589 and G3BP1 attenuated BJOE‐induced autophagy and apoptosis. Conclusion BJOE promotes autophagy and apoptosis through the hsa_circ_0001589/G3BP1/PAX6 axis in MCF‐7 breast cancer models, offering a novel therapeutic strategy for breast cancer and providing a circRNA‐mediated mechanism for natural anticancer drug research.